2019
DOI: 10.3892/or.2019.7125
|View full text |Cite
|
Sign up to set email alerts
|

Cellular response to glutamine and/or glucose deprivation in in�vitro transformed human fibroblasts

Abstract: Neoplastic transformation is characterized by metabolic rewiring to sustain the elevated biosynthetic demands of highly proliferative cancer cells. To obtain the precursors for macromolecule biosynthesis, cancer cells avidly uptake and metabolize glucose and glutamine. Thus, targeting the availability or metabolism of these nutrients is an attractive anticancer therapeutic strategy. To improve our knowledge concerning how cancer cells respond to nutrient withdrawal, the response to glutamine and/or glucose sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…A possible explanation for this effect may be the nuclear retention of TP53 due to its poly(ADP-ribosyl)ation that prevents TP53 interaction with the nuclear export receptor CRM1 [69]. Chiodi et al recently reported that glucose and/or glutamine deprivation causes very rapid PARP-1 activation and protein poly(ADP-ribosyl)ation [70]. This is consistent with the intracellular distribution of TP53 that was observed in all the tested cells grown in a low glucose medium (NC2) or glucose- and glutamine-free medium (NC3) (Figure 10C).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this effect may be the nuclear retention of TP53 due to its poly(ADP-ribosyl)ation that prevents TP53 interaction with the nuclear export receptor CRM1 [69]. Chiodi et al recently reported that glucose and/or glutamine deprivation causes very rapid PARP-1 activation and protein poly(ADP-ribosyl)ation [70]. This is consistent with the intracellular distribution of TP53 that was observed in all the tested cells grown in a low glucose medium (NC2) or glucose- and glutamine-free medium (NC3) (Figure 10C).…”
Section: Discussionmentioning
confidence: 99%
“…The change of GFP fluorescence intensity, normalized to the first timepoint of imaging of each cell (ΔF/F), was used to represent the fluctuation of cellular ATP levels. However, as deprivation of glucose only indirectly influences ATP concentrations and can impact other physiological responses, [31] we co-expressed photocaged Adk and the iATPSnFR sensor in HEK293T cells for the direct, non-invasive, and rapid depletion of cellular ATP. Genetically encoded Adk K13HCK was able to reduce ATP level upon optical triggering (10 s, microscope DAPI filter) to a greater extent than glucose deprivation, showing advantages in both specificity and dynamic capability (Figure 4c).…”
mentioning
confidence: 99%
“…S13 ). Depletion of glucose as a cancer cell energy source can cause cancer cells to die, whereas the generated H 2 O 2 can kill cancer cells as an oxidant [ 60 , 62 , 63 ]. Oxidation of glucose by GOX also affects the tumor environment in the form of enhanced hypoxia due to the consumption of O 2 and increased acidity by the production of d -gluconic acid [ 64 ].…”
Section: Resultsmentioning
confidence: 99%